The military enlightenment : war and culture in the French empire from Louis XIV to Napoleon - Pichichero, Christy, 1976- (Cornell University Press, 2017)
"Combines the study of literary works, treatises of moral philosophy, and archival military writings to show the ways that the military sphere both generated and applied French Enlightenment ideas with regard to the phenomenon of war, the human body and emotions, social equality, and human rights"--